Menggambar Kreatif dari Angka untuk Mengembangkan Imajinasi Anak Usia 4-5 Tahun - Malikatus Sholihah; Ulya Ainur Rofi’ah; Hilda Putri Nailil Izzah (Journal Ashil: Jurnal Pendidikan Anak Usia Dini, 2025)
This study aims to explore and enhance the creativity of 4-5-year-old children in drawing through a simple drawing technique using numbers at RA Muslimat NU Darul Ulum Ngembes. By utilizing numbers as a base, children are encouraged to develop their imagination into various forms of drawings. This research employs a descriptive method to illustrate the process and outcomes of applying this technique to Group A children. The data instruments and analysis techniques used help in understanding the extent to which drawing from numbers can foster early childhood creativity. The findings indicate that young children can easily transform numbers into creative drawing objects, significantly contributing to the development of their creative abilities. The results also show that this approach not only improves children's fine motor skills but also builds their confidence in expressing ideas visually. This study provides valuable insights for educators in employing simple yet effective approaches to stimulate creativity in early childhood, and highlights the importance of innovative learning methods in early education settings.